Imaging diagnosis in peripheral nerve injury - Dong, Yanzhao; Alhaskawi, Ahmad; Zhou, Haiying; Zou, Xiaodi; Liu, Zhenfeng; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Olga, Alenikova; Abdalbary, Sahar Ahmed; Chi, Yongsheng; Lu, Hui (Frontiers in Neurology, 2023)
Peripheral nerve injuries (PNIs) can be caused by various factors, ranging from penetrating injury to compression, stretch and ischemia, and can result in a range of clinical manifestations. Therapeutic interventions can vary depending on the severity, site, and cause of the injury. Imaging plays a crucial role in the precise orientation and planning of surgical interventions, as well as in monitoring the progression of the injury and evaluating treatment outcomes. PNIs can be categorized based on severity into neurapraxia, axonotmesis, and neurotmesis. While PNIs are more common in upper limbs, the localization of the injured site can be challenging. Currently, a variety of imaging modalities including ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI) and positron emission tomography (PET) have been applied in detection and diagnosis of PNIs, and the imaging efficiency and accuracy many vary based on the nature of injuries and severity. This article provides an overview of the causes, severity, and clinical manifestations of PNIs and highlights the role of imaging in their management.